2021
DOI: 10.1371/journal.pone.0258959
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ perspectives on a smartwatch intervention for children with ADHD: Rapid deployment and feasibility evaluation of a pilot intervention to support distance learning during COVID-19

Abstract: Distance learning in response to the COVID-19 pandemic presented tremendous challenges for many families. Parents were expected to support children’s learning, often while also working from home. Students with Attention Deficit Hyperactivity Disorder (ADHD) are at particularly high risk for setbacks due to difficulties with organization and increased risk of not participating in scheduled online learning. This paper explores how smartwatch technology, including timing notifications, can support children with A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 62 publications
0
2
0
2
Order By: Relevance
“…For example, a study of college students (aged 18-37 years) identified high rates of watch wearing behaviour (89.8%) across their study period and different usage patterns on weekdays (11.32 h, SD: 3.53) and weekends (8.66 h, SD: 3.60) [52]. While a study on children (aged 10-15 years) with neurodevelopmental disorders reported lower watch wearing patterns (5.66 h per day, SD: 3) because children only wanted to wear the watch while completing their school day [54]. Interestingly, in this study, the three oldest female participants had the lowest rate of watch wearing behaviour (28.6% to 35.7%) because they disliked the feeling of the watch on their wrist, and it is yet unclear whether this was due to JIA-related pain sensations.…”
Section: Watch Wearing Behaviourmentioning
confidence: 99%
“…For example, a study of college students (aged 18-37 years) identified high rates of watch wearing behaviour (89.8%) across their study period and different usage patterns on weekdays (11.32 h, SD: 3.53) and weekends (8.66 h, SD: 3.60) [52]. While a study on children (aged 10-15 years) with neurodevelopmental disorders reported lower watch wearing patterns (5.66 h per day, SD: 3) because children only wanted to wear the watch while completing their school day [54]. Interestingly, in this study, the three oldest female participants had the lowest rate of watch wearing behaviour (28.6% to 35.7%) because they disliked the feeling of the watch on their wrist, and it is yet unclear whether this was due to JIA-related pain sensations.…”
Section: Watch Wearing Behaviourmentioning
confidence: 99%
“…En el contexto de educación primaria y secundaria, Cibrian et al (2021) estudiaron la utilidad de los teléfonos y relojes inteligentes en el proceso educativo de alumnado con TDAH. Sus conclusiones apuntaban a que el uso de estos dispositivos mejoraba las habilidades organizativas de estos estudiantes, especialmente en periodos de educación a distancia donde las habilidades de organización fueron más importantes para la realización satisfactoria de las tareas.…”
Section: El Teléfono Móvil Como Parte De La Innovación Educativaunclassified
“…To understand the application of theory to practice through DHI, we engage user-center design methods, including co-design with children with ADHD and early user testing and engagement with caregivers (parents and teachers) ( 20 ). We are now testing CoolCraig, a mobile and smartwatch application to support a token economy and zone of regulation strategies in a family setting, which resulted from this blend of theoretical and empirical design work ( 21 ). We will continue to iterate on this system with the ultimate goal of creating a stable version for an RCT and eventual translation to clinical and educational practice.…”
Section: Life Cyclesmentioning
confidence: 99%